ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PENGGUNAAN TRANSPORTASI PRIBADI PADA MAHASISWA MENGGUNAKAN PENDEKATAN PARTIAL LEAST SQUARE (Studi Kasus pada Universitas Diponegoro Semarang) - Martyanto Tedjo; Sugito Sugito; Suparti Suparti (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2017)
The process of structural development in developing countries is a must. Each sector that developed is related to one another. These sectors associated with the supporting factor named transport, means transport has a vital and strategic functions in the development of other sectors. Education is one of the construction sector that growing rapidly, especially in big cities, and transportation is one of the factors supporting it: since schools and universities is one of the important generator of domestic transportation network. Each university holds up to tens of thousands of new college students every year. In this point, the transport activity in big cities is becoming increasingly complex, due to the increase in the private transportation is not matched by the increase in roads, causing congestion. Factors that influence the decision of the use of private transport on the student comprehensively analyzed using structural equation based on the variance, Partial Least Square (PLS). PLS is a powerful analytical method, though it’s not based on many assumptions (soft model), for example, the multivariate normal assumptions, it can use nominal scale up to ratios, as well as the sample size shouldn’t be large. PLS estimates the model od relationship between latent variables and also latent variables with the indicator. Based on the analysis we concluded that the decision on the use in private transportations of Diponegoro University students affected by a combination of latent variables such time management, cost, physical, social interaction, and the intervening variable perception of 68.28%.Keywords: transportation, using of private transportation, Partial Least Square (PLS)